2023
DOI: 10.3389/fendo.2023.1211473
|View full text |Cite
|
Sign up to set email alerts
|

Linsitinib, an IGF-1R inhibitor, attenuates disease development and progression in a model of thyroid eye disease

Abstract: IntroductionGraves’ disease (GD) is an autoimmune disorder caused by autoantibodies against the thyroid stimulating hormone receptor (TSHR) leading to overstimulation of the thyroid gland. Thyroid eye disease (TED) is the most common extra thyroidal manifestation of GD. Therapeutic options to treat TED are very limited and novel treatments need to be developed. In the present study we investigated the effect of linsitinib, a dual small-molecule kinase inhibitor of the insulin-like growth factor 1 receptor (IGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…Thus, we obtained bone marrow samples from each 10 BALB/c mice that were (i) immunized with the A-subunit of the TSHR and not further treated, (ii) immunized and treated with linsitinib or that were (iii) control-immunized with non-immunogenic ß-Gal and not further treated. Development of TED and changes in the orbit in these mice has been previously reported ( 18 ). These studies demonstrated that 90% of the mice that were immunized with TSHR developed TED.…”
Section: Methodssupporting
confidence: 57%
See 3 more Smart Citations
“…Thus, we obtained bone marrow samples from each 10 BALB/c mice that were (i) immunized with the A-subunit of the TSHR and not further treated, (ii) immunized and treated with linsitinib or that were (iii) control-immunized with non-immunogenic ß-Gal and not further treated. Development of TED and changes in the orbit in these mice has been previously reported ( 18 ). These studies demonstrated that 90% of the mice that were immunized with TSHR developed TED.…”
Section: Methodssupporting
confidence: 57%
“…Mice were immunized as described below at an age of 6 weeks. We employed three groups of mice ( 18 ), i.e. healthy control mice immunized with non-immunogenic ß-Gal (n=10), TSHR immunized mice (n=10) and TSHR immunized mice that were treated with linsitinib (n=10).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This pattern prompted us to investigate the effects of manipulating the IGF-1 pathway on adipogenesis in orbital fibroblasts. We utilized linsitinib, a small molecule IGF-1R antagonist, which diminishes immune infiltration and fibrosis in the orbit in TED animal models (41). Currently, linsitinib is undergoing Phase 2 clinical trials as a potential oral therapy for TED.…”
Section: Linsitinib Treatment Reduces Adipogenesis In Ted Fibroblastsmentioning
confidence: 99%